Master Card - Janakiramayya, Pasupuleti (International Journal of Computer Sciences and Engineering, 2019)
The master card project is all about integrating the currently available provisions by government of India along with few enhancements like linking DNA (Deoxyribonucleic Acid) of Humans with their permanent account number (PAN), QR code which assists a person in various ways like knowing his/her details, payments etc. and Integrated chip which can be read in a device when scanned. These are the provisions of the project which are partially taken from the existing services of government of India like Aadhar and few are additionally added from my end to improve effective administration. It helps the citizens of India to effectively connect with the government and avail its services. It helps the government of India to reduce corruption, ensures its schemes are implemented in proper way (delivering services to right means of people), It helps Indian judicial services to sort out pending cares and in giving judgment quickly likewise things etc. It creates a platform for government of India to bring all the citizens of India on one page and administer them effectively.